1995
DOI: 10.1096/fasebj.9.8.7768361
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the neurotrophic factor sequence of prosaposin

Abstract: Prosaposin, recently identified as a neurotrophic factor (1), is the precursor of saposins A, B, C, and D. The neurotrophic activity of prosaposin resides in the saposin C domain. We have pinpointed the active sequence to a linear 12-mer located in the NH2-terminal sequence of saposin C (LIDNNKTEKEIL). Nanomolar concentrations of a 22-mer peptide encompassing this region stimulated neurite outgrowth and choline acetyltransferase activity, and prevented cell death in neuroblastoma cells. In primary cerebellar g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 24 publications
2
113
0
Order By: Relevance
“…A sharp drop in binding of the peptides was observed with losses of sequences in the region between 6 and 21. As a further note, domain 1 has been shown to promote neurite outgrowth in culture suggesting a separate function for this portion of the molecule (O'Brien et al, 1995). From the deletional analyses with synthetic peptides, we have shown that residue Asn 22, which is the glycosylation site of native saposin C, is located within the binding site (but outside the activation site) of domain 1.…”
Section: Characterization Of the Functional Domainsmentioning
confidence: 70%
“…A sharp drop in binding of the peptides was observed with losses of sequences in the region between 6 and 21. As a further note, domain 1 has been shown to promote neurite outgrowth in culture suggesting a separate function for this portion of the molecule (O'Brien et al, 1995). From the deletional analyses with synthetic peptides, we have shown that residue Asn 22, which is the glycosylation site of native saposin C, is located within the binding site (but outside the activation site) of domain 1.…”
Section: Characterization Of the Functional Domainsmentioning
confidence: 70%
“…We can exclude the concept that N215K mutated prosaposin protein can be defective as a neurotrophic factor: 7,8 in fact, the portion of the protein involved in this role lies in the sap-C region. To date five other MLD-causing sap-B mutations have been identified in the PSAP gene.…”
Section: Discussionmentioning
confidence: 99%
“…However, this disease phenotype appears also, when functional sap-B is absent. 1 A neurotrophic function of the precursor prosaposin protein itself has been elucidated, 7,8 and a role in ganglioside binding and transport has been hypothesized. 9 Recently, the structure of a saposin-like protein, porcine NK-lysin, representative of a family of sequence related proteins sharing a possible common fold, has been determined, comprising five amphipathic α-helices, one at the centre, the others at the two opposite sides, folded into a single globular domain with three disulphide bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Proteolytic processing of prosaposin gives rise to four sphingolipid activator proteins named saposins A, B, C, and D that are localized within lysosomes and that activate the hydrolysis of sphingolipids by lysosomal hydrolases. In addition to its role as a lysosomal precursor protein, prosaposin is active as a neurotrophic factor eliciting neuronal differentiation and triggering a signal cascade after binding to a cell surface receptor (2)(3)(4). Recently mitogen-activated protein kinase (MAPK) activation has been shown for prosaposin in PC12 cells (4).…”
mentioning
confidence: 99%